Universal design of a system for liquid–liquid microextraction: green determination of nitrate in vegetable and water samples by automated magnetic stirring-assisted dispersive liquid–liquid microextraction - Šandrejová, Jana; Gajdošová, Andrea; Serbin, Rastislav; Balogh, Ioseph (Analytical methods, 2025)
This article highlights a new approach for liquid–liquid microextraction, which takes into account the possibility of using one flow-based system for various automated microextraction modes. This design for the microextraction process in combination with an optical probe was proposed and successfully tested for dispersive liquid–liquid microextraction (DLLME), air-assisted dispersive liquid–liquid microextraction (AA-DLLME) and magnetic stirring-assisted dispersive liquid–liquid microextraction (MSA-DLLME) of nitrate. The results showed that the proposed system is simple and enables an easy change of the operation protocol. The system was applied to the determination of NO 3 − in the form of an ion associate with the malachite green reagent. Under optimized conditions, the best sensitivity of determination was achieved by MSA-DLLME. The calibration graph was linear over the concentration range of 0.2–10 mg L −1 NO 3 − . The LOD was 0.008 mg L −1 NO 3 − . The procedure was applied to the determination of nitrate in vegetable and water samples. The applied procedure was compared with ion chromatography approaches and evaluated using metrics, including the Analytical Greenness Metric Approach (AGREE) for greenness, the most current Blue Applicability Grade Index (BAGI) for blueness, and the more inclusive RGB 12 algorithm for whiteness assessment. The evaluation shows high overall scores for the presented procedure. This article highlights a new approach for liquid–liquid microextraction, which takes into account the possibility of using one flow-based system for various automated microextraction modes.